Terminalia catappa Extract Palliates Redox Imbalance and Inflammation in Diabetic Rats by Upregulating Nrf-2 Gene - Franklyn Nonso Iheagwam; Gaber El-Saber Batiha; Olubanke Olujoke Ogunlana; Shalom Nwodo Chinedu (International Journal of Inflammation)
This study aims at evaluating the ameliorative role of Terminalia catappa aqueous leaf extract (TCA) on hyperglycaemia-induced oxidative stress and inflammation in a high-fat, low dose streptozotocin-induced type 2 diabetic rat model. Experimental rats were treated orally with 400 and 800 mg/kg bw TCA daily for four weeks. Antioxidant enzyme activities, plasma glucose concentration, protein concentration, oxidative stress, and inflammation biomarkers were assayed using standard methods. Hepatic relative expressions of tumour necrosis factor-alpha (TNF-α), interleukin-six (IL-6), and nuclear factor-erythroid 2 related factor 2 (Nrf-2) were also assessed. Molecular docking and prediction of major TCA phytoconstituents’ biological activity related to T2DM-induced oxidative stress were evaluated in silico. Induction of diabetes significantly (p<0.05) reduced superoxide dismutase, glutathione-S-transferase, and peroxidase activities. Glutathione and protein stores were significantly (p<0.05) depleted, while glucose, MDA, interleukin-six (IL-6), and tumour necrosis factor-α (TNF-α) concentrations were significantly (p<0.05) increased. A significant (p<0.05) upregulation of hepatic TNF-α and IL-6 expression and downregulation (p<0.05) of Nrf-2 expression were observed during diabetes onset. TCA treatment significantly (p<0.05) modulated systemic diabetic-induced oxidative stress and inflammation, mRNA expression dysregulation, and dysregulated macromolecule metabolism. However, only 800 mg/kg TCA treatment significantly (p<0.05) downregulated hepatic TNF-α expression. 9-Oxabicyclo[3.3.1]nonane-2,6-diol and 1,2,3-Benzenetriol bound comparably to glibenclamide in Nrf-2, IL-6, and TNF-α binding pockets. They were predicted to be GST A and M substrate, JAK2 expression, ribulose-phosphate 3-epimerase, NADPH peroxidase, and glucose oxidase inhibitors. These results suggest that TCA ameliorates hyperglycaemia-induced oxidative stress and inflammation by activating Nrf-2 gene.